(untitled) (JURKAM: Jurnal Konseling Andi Matappa, 2017)
Qualitative as the "art of understanding" is passed on as the expertise of the researcher to understand the object of research with the sophisticated efforts done through the art of speaking, the art of writing and the art of presenting what has been studied, as we can find in artists that produce fine art. Understanding qualitative research methods in guidance and counseling is viewed as an art. The term understand in qualitative research is the process of grasping the meaning of a phenomenon that is the target of interpretation in a study. In the implementation of guidance and counseling services, counselor seeks to understand the meaning of the problems of the counselee with the effort to capture the meaning or meaning of problematic faced by the counselee. The art of understanding qualitative research in guidance and counseling is a deep understanding of research methods that describe the object of research through procedures and data that are non numerical to the object of research, such as verbal data, text data, content analysis techniques, conversion analysis techniques, focus groups, analysis Discourse, and phenomenology to interpret the object of service phenomenon Guidance and Counseling.